Customer Engagement in Higher Education: How Important the Role of Social Media Marketing, E-Service Quality, and E-Satisfaction for Generation Z Students? - Freddy Pandapotan Simbolon; Lena Yanti (The Winners, 2021)
The goal of the research was to examine the effect of social media marketing, e-service quality, and e-satisfaction on customer engagement. The research was conducted at Bina Nusantara University (Binus) with a sample of 100 students  from Generation Z using quantitative approach with data collection by distributing questionnaires to be analyzed using path analysis. The findings show that social media marketing and e-service quality significantly have impacts on e-satisfaction and customer engagement, while the e-satisfaction does not significantly impact customer engagement.  Therefore, the development of digital technology in higher education becomes the main focus for supporting services and activities.